2011
DOI: 10.1016/j.jsps.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the medication history at admission to hospital in Saudi Arabia

Abstract: Inaccurate medication history at admission to a hospital was common in Saudi Arabia. This has the potential to cause harm to patients if it remains undetected. Pharmacists could potentially play a major role in obtaining this medication history at the time of hospital admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 15 publications
4
34
0
Order By: Relevance
“…Participants and investigators enrolling participants could not foresee the study group assignment 4 Participants and investigators enrolling participants could possibly foresee the study group assignments 5 Insufficient information permit judgment of 'Low risk' or 'High risk' 8 M A N U S C R I P T…”
Section: Selection Bias (Allocation Concealment)mentioning
confidence: 99%
See 1 more Smart Citation
“…Participants and investigators enrolling participants could not foresee the study group assignment 4 Participants and investigators enrolling participants could possibly foresee the study group assignments 5 Insufficient information permit judgment of 'Low risk' or 'High risk' 8 M A N U S C R I P T…”
Section: Selection Bias (Allocation Concealment)mentioning
confidence: 99%
“…Poor communication of clinical information at healthcare transitions is 32 responsible for over 50% of all medication errors and up to 20% of adverse events. [1][2][3][4] …”
mentioning
confidence: 99%
“…Earlier studies found that inconsistencies in medication histories occur in up to 60% of admitted patients 21–28. Pharmacists could decrease these errors by obtaining a medication history at the time of admission and discharge 29 30…”
Section: Discussionmentioning
confidence: 99%
“…[16] However, this observation is not entirely surprising, as findings from previous studies on the content of referral documents in Nigeria and other developing countries reflect a picture of inadequate, inaccurate (or inappropriate) information. [15,17,18] This situation engenders low-quality referrals and may not be entirely unconnected to the lack of a universally adopted or acceptable "gold standard" for referral documentation.…”
Section: The Most Relevant Information (Or "Tool") Expected In Referralsmentioning
confidence: 99%